PROGRAM BIMBINGAN PERNIKAHAN BERBASIS PEMULIHAN TRAUMA RELASIONAL BAGI PEREMPUAN PASCA PERCERAIAN: PENGEMBANGAN MATERI ACUAN KONSELING - Budiarda Widya Laksana Budiarda (AflahConsilia : Jurnal Bimbingan dan Konseling, 2026)
The high divorce rate in Indonesia, particularly in Ngawi Regency where the majority of cases are filed by wives, presents serious psychological challenges for post-divorce women planning to remarry. This study aims to develop comprehensive, evidence-based marriage guidance reference materials for divorced women, focusing on relational trauma recovery as the foundation for remarriage readiness. This study employs a library research approach with a systematic analysis of Scopus-indexed empirical literature from 2015–2025. Integrated theories include Adult Attachment Theory (Bowlby), Trauma Recovery Theory (Herman), Cognitive-Behavioral Therapy, and the Gottman Method Couples Therapy. The findings indicate that marriage readiness in post-divorce women requires multilayered interventions encompassing: (1) relational trauma recovery and cognitive schema restructuring regarding marriage; (2) strengthening emotion regulation and secure attachment patterns; (3) developing assertive communication and conflict resolution skills; and (4) marriage readiness assessment based on emotional, cognitive, social, and interpersonal dimensions. This article produces a modular design of a five-session thematic marriage guidance program adaptable by counselors at Religious Affairs Offices (KUA) and Islamic counseling institutions. The contribution of this research is expected to address the gap in pre-marital guidance services that have not specifically targeted post-divorce women. Keywords: marriage guidance; divorce; relational trauma; marriage readiness; Islamic counseling